2007
DOI: 10.1242/dev.02764
|View full text |Cite
|
Sign up to set email alerts
|

Controlled overexpression of Pax6 in vivo negatively autoregulates thePax6locus, causing cell-autonomous defects of late cortical progenitor proliferation with little effect on cortical arealization

Abstract: Levels of expression of the transcription factor Pax6 vary throughout corticogenesis in a rostro-lateral high to caudo-medial low gradient across the cortical proliferative zone. Previous loss-of-function studies have indicated that Pax6 is required for normal cortical progenitor proliferation, neuronal differentiation, cortical lamination and cortical arealization, but whether and how its level of expression affects its function is unclear. We studied the developing cortex of PAX77 YAC transgenic mice carryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 54 publications
11
106
1
Order By: Relevance
“…These results are congruent with the PAX77 YAC transgenic mice, carrying several copies of human PAX6, and also show normal thalamocortical projections (Manuel et al, 2007). Recent evidence suggests that COUP-TF1 endows positional specification that controls the areal size and position as well as targeting of area-specific thalamocortical projections (Armentano et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These results are congruent with the PAX77 YAC transgenic mice, carrying several copies of human PAX6, and also show normal thalamocortical projections (Manuel et al, 2007). Recent evidence suggests that COUP-TF1 endows positional specification that controls the areal size and position as well as targeting of area-specific thalamocortical projections (Armentano et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…Overexpression of Pax6 in cortex of transgenic mice had little effect on areal targeting of thalamocortical connectivity (Manuel et al, 2007), and our current findings indicate, that although the cortex of the Pax6cKO mice is molecularly caudalized, the thalamocortical connectivity remains unchanged.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…This dose-response analysis revealed that the increase of ␣ cells and of glucagon transcripts was maximal with 1.5 ng of injected Mo2 corresponding to a mild reduction of pax6b activity. Previous studies have shown that a precise range of the Pax6 protein level is important for the proper development of the eyes, brain, and pancreas because an increase of Pax6 expression in transgenic mice leads to abnormalities in these organs (19,20,34). Moreover, heterozygous Pax6 individuals display anomalies in eye morphology and brain patterning (10).…”
Section: Discussionmentioning
confidence: 99%
“…Through binding to different DNA sequences via usage of various DNA binding motifs alone or in combination, PAX6 controls the expression of various downstream target genes involved in complex gene regulatory networks for cell proliferation, adhesion, migration, and neurogenesis (Schmahl et al, 1993;Caric et al, 1997;Sander et al, 1997;Sax et al, 1997;Tang et al, 1997;Duncan et al, 1998;Beimesche et al, 1999;Meech et al, 1999;Singh et al, 2000;Sivak et al, 2000;Zhou et al, 2000;Chauhan et al, 2002;Mishra et al, 2002;SkalaRubinson et al, 2002;Zhou et al, 2002;Andrews and Mastick, 2003;Davis et al, 2003;Horie et al, 2003;Tyas et al, 2003;Cvekl et al, 2004;Grinchuk et al, 2005;Mayes et al, 2006;Holm et al, 2007;Tuoc and Stoykova, 2008). Not only reduced, but also increases level of PAX6 gene dosage also cause defects in developmental processes that are sensitive to PAX6 dosage, including eye organogenesis and corticogenesis (Schedl et al, 1996;Berger et al, 2007;Manuel et al, 2007).…”
Section: Functionmentioning
confidence: 99%